Answer:
The solution of given equation is (2,5)
Step-by-step explanation:
The equations give to us are:
y - 3 = x
or
y = x + 3
y = x² - 6x + 13
We can find the solution of the given system of equations by substituting each point in both of the equations. The point which satisfies both of the equation will be the solution of the the system of given equation.
Substitute (2,5) in both equations
y = x+3
5 = 2+3
5 = 5
TRUE
y = x² - 6x + 13
5 = 2² -6(2) + 13
5 = 5
TRUE
Similarly, we can also check the rest of the points, which come as FALSE.
Therefore, the solution of given equation is (2,5)